2018
DOI: 10.1108/ec-04-2016-0142
|View full text |Cite
|
Sign up to set email alerts
|

Solitary wave collisions by double-dam-broken simulations with the MPS method

Abstract: Purpose The paper aims to apply a modified version of the MPS method to a double-dam-breaking test in which high dispersion zones and high natural clusterization zones are present, such as when the water column collapses into two sides and the two solitary waves collide, respectively. Design/methodology/approach The work takes advantage of the mixed source term from the cheaper computational version of the moving particle semi-implicit (MPS) method to reduce one step from the MPS classical algorithm. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The interaction radius used in this study is r 0 = 2.1l 0 , where l 0 is the initial distance between particles. The pressure gradient term used in this work is given by the formulation proposed by Sanchez-Mondragon [58], because it provides a stable approach for simulating solitary waves as it has been shown in Sanchez-Mondragon and Vazquez-Hernandez [59]. Moreover, in Sanchez-Mondragon [58], it is shown that this pressure gradient term reduces the overestimated interparticle pressure force magnitudes that are present in other pressure gradient (20) models.…”
Section: Numerical Methods Implementation Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…The interaction radius used in this study is r 0 = 2.1l 0 , where l 0 is the initial distance between particles. The pressure gradient term used in this work is given by the formulation proposed by Sanchez-Mondragon [58], because it provides a stable approach for simulating solitary waves as it has been shown in Sanchez-Mondragon and Vazquez-Hernandez [59]. Moreover, in Sanchez-Mondragon [58], it is shown that this pressure gradient term reduces the overestimated interparticle pressure force magnitudes that are present in other pressure gradient (20) models.…”
Section: Numerical Methods Implementation Detailsmentioning
confidence: 99%
“…The pressure gradient term used in this work is given by the formulation proposed by Sanchez-Mondragon [58], because it provides a stable approach for simulating solitary waves as it has been shown in Sanchez-Mondragon and Vazquez-Hernandez [59]. Moreover, in Sanchez-Mondragon [58], it is shown that this pressure gradient term reduces the overestimated interparticle pressure force magnitudes that are present in other pressure gradient (20) models. In the case of wavemakers, natural clusterization appears when the paddle moves forward to generate waves, so this pressure gradient term aids to maintain a stable simulation, that is, where d is the number of space dimensions, n 0 is the constant particle number density, and P i is the minimum value of P j neighboring particles, jmin =î .…”
Section: Numerical Methods Implementation Detailsmentioning
confidence: 99%
See 3 more Smart Citations